2020
DOI: 10.1186/s12964-020-00670-2
|View full text |Cite
|
Sign up to set email alerts
|

The biology of tardigrade disordered proteins in extreme stress tolerance

Abstract: Disordered proteins have long been known to help mediate tolerance to different abiotic stresses including freezing, osmotic stress, high temperatures, and desiccation in a diverse set of organisms. Recently, three novel families of intrinsically disordered proteins were identified in tardigrades, microscopic animals capable of surviving a battery of environmental extremes. These three families include the Cytoplasmic-, Secreted-, and Mitochondrial- Abundant Heat Soluble (CAHS, SAHS, and MAHS) proteins, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
111
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(112 citation statements)
references
References 91 publications
(156 reference statements)
1
111
0
Order By: Relevance
“…Result 1: TDPs can protect recombinant strains based on E. coli BL21 under conditions of lyophilization, allowing them to be preserved at room temperature [23] . CAHS 106094 expression in BL21 resulted in the highest survival rate at room temperature after lyophilization.…”
Section: Resultsmentioning
confidence: 99%
“…Result 1: TDPs can protect recombinant strains based on E. coli BL21 under conditions of lyophilization, allowing them to be preserved at room temperature [23] . CAHS 106094 expression in BL21 resulted in the highest survival rate at room temperature after lyophilization.…”
Section: Resultsmentioning
confidence: 99%
“…These proteins are highly expressed constitutively or significantly enriched in response to desiccation (e.g. [ 18 , 19 ],) but seem to be missing in some tardigrades, suggesting that anhydrobiosis in tardigrades cannot be attributed solely to TDPs [ 20 , 21 ]. However, available data appear to support a common and important role of proper mitochondria function in anhydrobiosis.…”
Section: Introductionmentioning
confidence: 99%
“…It is The copyright holder for this preprint this version posted June 22, 2021. ; https://doi.org/10.1101/2021.06. 22.449423 doi: bioRxiv preprint 3 their biological components or cell membrane without water. Early studies on desiccation tolerance identified the disaccharide trehalose and the late embryogenesis abundant (LEA) proteins as the functional mediators of anhydrobiosis (9).…”
Section: Introductionmentioning
confidence: 99%
“…In extremotolerant tardigrades, through heat-soluble proteomics in a search for LEA and LEAlike proteins, highly hydrophilic and heat-soluble protein families have been identified as cytosolic abundant heat-soluble (CAHS) proteins (19)(20)(21)(22). Although these proteins are distinct from LEA proteins based on their conserved sequences, they share some similarities with LEA proteins in terms of the bioinformatic prediction of high propensity for α-helix formation (19,20).…”
Section: Introductionmentioning
confidence: 99%